1999
DOI: 10.1074/jbc.274.7.4115
|View full text |Cite
|
Sign up to set email alerts
|

Probability Analysis of Variational Crystallization and Its Application to gp120, The Exterior Envelope Glycoprotein of Type 1 Human Immunodeficiency Virus (HIV-1)

Abstract: The extensive glycosylation and conformational mobility of gp120, the envelope glycoprotein of type 1 human immunodeficiency virus (HIV-1), pose formidable barriers for crystallization. To surmount these difficulties, we used probability analysis to determine the most effective crystallization approach and derive equations which show that a strategy, which we term variational crystallization, substantially enhances the overall probability of crystallization for gp120. Variational crystallization focuses on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 57 publications
1
80
0
Order By: Relevance
“…The various biochemical manipulations (such as deglycosylation for gp120 and papain digestion to produce Fab 17b), protein purification and ternary complex crystallization are described elsewhere 25 . The best crystals were small needles of cross-section only 30-40 μm.…”
Section: Methods Protein Production Crystallization and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various biochemical manipulations (such as deglycosylation for gp120 and papain digestion to produce Fab 17b), protein purification and ternary complex crystallization are described elsewhere 25 . The best crystals were small needles of cross-section only 30-40 μm.…”
Section: Methods Protein Production Crystallization and Data Collectionmentioning
confidence: 99%
“…We made truncations at termini and variable loops in various combinations with gp120 from various strains, extensively deglycosylated these gp120 variants, and produced complexes with various ligands. A theoretical analysis indicated that the probability of crystal formation is greatly increased by such reduction of surface heterogeneity and trials with multiple variants 25 . After screening almost twenty combinations of gp120 variants and ligands, we obtained crystals 25 of a ternary complex composed of a truncated form of gp120, the N-terminal two domains (DID2) of CD4, and a Fab from the human neutralizing monoclonal antibody 17b (ref.…”
Section: Structure Determinationmentioning
confidence: 99%
“…Q425 Fab was prepared by papain digestion of reduced and alklated IgG following methods described in ref. 19.…”
Section: Methodsmentioning
confidence: 99%
“…Removing disordered regions may thus improve homogeneity. The energetics and kinetics of protein crystallization may be facilitated by selective deletion of these unstructured sequences (5). Even those proteins that readily crystallize can suffer from poor diffraction, and it is likely that disorder plays a significant role.…”
mentioning
confidence: 99%